Validation of force fields of rubber through glass-transition temperature calculation by microsecond atomic-scale molecular dynamics simulation - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Journal of Physical Chemistry B, 2016)
Microsecond atomic-scale molecular dynamics simulation has been employed to calculate the glass-transition temperature (T-g) of cis- and trans-1,4-polybutadiene (PB) and 1,4-polyisoprene (PI). Both all-atomistic and united-atom models have been simulated using force fields, already available in literature. The accuracy of these decade old force fields has been tested by comparing calculated glass-transition temperatures to the corresponding experimental values. T-g depicts the phase transition in elastomers and substantially affects various physical properties of polymers, and hence the reproducibility of T-g becomes very crucial from a thermodynamic point of view. Such validation using T-g also evaluates the ability of these force fields to be used for advanced materials like rubber nanocomposites, where T-g is greatly affected by the presence of fillers. We have calculated T-g for a total of eight systems, featuring all-atom and united-atom models of cis- and trans-PI and-PB, which are the major constituents of natural and synthetic rubber. Tuning and refinement of the force fields has also been done using quantum-chemical calculations to obtain desirable density and T-g. Thus, a set of properly validated force fields, capable of reproducing various macroscopic properties of rubber, has been provided. A novel polymer equilibration protocol, involving potential energy convergence as the equilibration criterion, has been proposed. We demonstrate that not only macroscopic polymer properties like density, thermal expansion coefficient, and T-g but also local structural characteristics like end-to-end distance (R) and radius of gyration (R-g) and mechanical properties like bulk modulus have also been equilibrated using our strategy. Complete decay of end-to-end vector autocorrelation function with time also supports proper equilibration using our strategy.

Impact of plasticizer addition on molecular properties of polybutadiene rubber and its manifestations to glass transition temperature - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Macromolecular Theory and Simulations, 2019)
Effect of blending low and high T-g polymer on the structural, spatial, and temporal properties of the polybutadiene rubber are investigated using molecular dynamics simulations. It is elucidated that smaller chain length counterpart of polybutadiene (5mer-OB) acts as plasticizer for the polybutadiene rubber matrix (32mer-PB). Observed flexibility at macroscopic level by plasticizer addition is corroborated at the molecular level in the form of lower conformational rigidity and faster diffusion of polybutadiene chains in the mixtures. It is inferred that plasticizers decreases T-g of the matrix, due to cooperative influence of decreased chain packing and rigidity. Opposite effect is observed in mixtures with high T-g polymer, polystyrene. T-g of the mixtures showed substantial dependence on the type, concentration, chain length as well as miscibility of plasticizers in the matrix. However, the effect of increasing chain length is more pronounced but counter-controlled by the spatially heterogeneous distribution of the plasticizer. Clustering of polystyrene chains induced significant dynamic heterogeneity in the homogeneous polybutadiene matrix, which apparently lead to reduced plasticization effect. Addition of plasticizers in rubber induce discernible changes in the structural and dynamic properties of the rubber matrix, which manifest as the variation in glass transition and explains the real-life activity of plasticizers.
Keywords: Glass transition temperature; MD Simulation; plasticizer action; polybutadiene rubber; Polystyrene; spatial and dynamic heterogeneity